Numerical assessment of the effects of carbon deposition and oxidation on chemical looping combustion in a packed-bed reactor. (16th March 2017) - Diglio, Giuseppe; Bareschino, Piero; Mancusi, Erasmo; Pepe, Francesco
Abstract: Chemical looping combustion with methane as fuel in a packed-bed reactor using Ni as oxygen carrier was numerically investigated. To this aim, a mathematical model that takes into account both oxidation and reduction phases was developed. To describe catalyst fouling due to carbon deposition, CH4 decomposition and carbon regasification by steam and CO2 (Boudouard reaction) were considered during reduction phase, while carbon combustion was taken into account during oxidation phase. A catalyst deactivation function due to carbon accumulation on oxygen carrier was introduced too. In the paper the effects of fouling on the operability of packed-bed reactor was studied, focusing the attention on the switch strategy adopted. Results show that a detailed description of carbon deposition and consumption phenomena is an essential prerequisite to properly operate a CLC process. Indeed, it was found that working with variable oxidation and reduction time lengths, the power produced is about three times greater than of that obtainable operating with fixed times. Although carbon deposition can be also reduced by increasing the H2 O:CH4 feed ratio, it was found that in this case the power produced decreases by about 30% with respect to that obtained operating with variable oxidation and reduction time lengths. Abstract : Graphical abstract: Abstract : Highlights: A mathematical model for Chemical Looping Combustion (CLC) has been developed. The effect of carbon deposition/oxidation has been investigated. CLC performances hinge on the time-length of both oxidation and reduction phase. Dynamically adjust the time lengths ensure highest reactor performances. Optimal operating conditions for sustained cyclic operation are presented.